Comment on ‘Genetic evidence and new morphometric data as essential tools to identify the Patagonian seahorse Hippocampus patagonicus (Pisces, Syngnathidae) by González et al. (2014)’ - Luzzatto, Diego (2014)
The aim of the contribution of González et al. (2014) was to improve the original description and validate the taxonomic status of the Patagonian seahorse Hippocampus patagonicus Piacentino & Luzzatto 2004. To do so, the authors analysed morphological and genetic characteristics of seahorses of San Antonio Bay, Argentina. Concerning both issues, the information presented lacks validity and originality.